Performance, stock selection ability, timing ability and persistence in bull and bear phase: a Malaysian unit trust study - Cheong, Jiunn Yan (2019)
This study aims to examine the performance, stock selection ability, market timing ability, and persistence of Malaysian unit trusts in different market condition. We found that in bull phases, unit trusts are more likely to outperform the market. Similarly to the performance on annual basis, equity funds were most likely to outperform the market compared to other fund styles. The outperformance of these unit trust were due to the manager’s superior stock selection ability, with also equity fund managers more likely to have superior stock selection ability compared to other funds style. Most unit trust managers, regardless of fund style, have poor timing ability. Most Malaysian unit trust were found to have lack stock selection ability and have poor market timing ability across both market state. There is a trade-off between stock selection ability and market timing ability. For persistence of unit trust performance, we found no conclusive pattern in any market state.